AVALIAÇÃO DA NUTRIÇÃO NA CAPACIDADE DA RESPOSTA IMUNOLÓGICA DE CAMUNDONGOS C57BL/6 ATRAVÉS DA ADMINISTRAÇÃO DE DIETA INDUTORA DE OBESIDADE E DIETA À BASE DE AMINOÁCIDOS DURANTE A INFECÇÃO POR Leishmania infantum. - Sarnaglia, Glenia Daros (2020)
It has long been accepted that immunity or susceptibility to disease depends on the measure of nutrition. Nutritional imbalances affect the ability to host the protective inflammatory response, causing damage to immune defenses. Many of these mechanisms r